The shift of Acehnese language: A sociolinguistic study to preserve regional languages - Maria Ulfa; Irma Dewi Isda; Purwati Purwati (Studies in English Language and Education, 2018)
This study uses a case study research method with a qualitative study design. The aims of the study were to find out the domains of Acehnese language shifts in Langsa and the reasons why Acehnese teenagers are shifting their language. Five districts in Langsa, one of the cities in Aceh, Indonesia, became the research location. They were Langsa Kota, Langsa Barat, Langsa Timur, Langsa Baroe and Langsa Lama. The respondents were Acehnese young adults within the age range of 18 to 21 years old. There were 10 respondents from each district, making a total of 50 respondents. The instruments used in this study were observations, a questionnaire, and interviews. Simple statistics were used to analyse the questionnaire, meanwhile the data analysis for the observations and interviews followed an interactive model from Miles and Huberman, namely: data reduction, data display, verification of data, and conclusions. The results showed that the domains of education (30 respondents) and of friendship (27 respondents had the largest number of shifters. Meanwhile, the family domain had the least shifts, so it was concluded that shifts rarely occurred in this domain. Finally, there are three fundamental factors that influenced the shift: environment, habitual usage, and choice of language.